Histological Structure of the Kidney in the Iraqi Pin-tailed Sandgrouse Pterocles Alchata (Linnaeus, 1766) Bird - Obaid, Wafaa Barghash; A. Al-Bakri, Nahla (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The current study was conducted on six adult males of the Iraqi pin-tailed sandgrouse, Pterocles alchata, to determine the histological structure of the kidneys. The results showed that each kidney consists of three lobes: cranial, middle, and caudal. Histological results showed that the kidneys consist of the cortex and the medullary, and the cortex forms the majority of the kidney, which consists of large and small renal corpuscles. Each renal corpuscle consists of the Bowman capsule, glomerulus, the proximal convoluted tubule, which is lined with simple cuboidal epithelium tissue with a brush border, the distal convoluted tubules, and the collecting tubules, which are lined with simple cuboidal epithelium tissue. The medullary area contains thin and thick segments of the Henle loop, arranged around the medullary cones, and a simple cuboidal epithelium-lined collecting duct from the middle part of the cone.